Improved O-LEACH protocol: A clustering based approach in wireless microsensor network - Pooja; Singh, Surendra (2016 10th International Conference on Intelligent Systems and Control (ISCO), 2016)
Wireless sensor network is one of the emerging technologies in wireless networks and communication. WSN composed of large number of small sensors which senses the physical situations occurred in the environment. For WSNs, energy efficiency is the main challenge and to create efficient networks, sophisticated routing algorithms are designed. Clustering algorithm is one of technique used in WSN to minimize the energy consumption but the major challenge in clustering algorithm is the selection of cluster head. In this paper, we will discuss about energy efficient routing protocol, Improved O-LEACH; which employs clustering algorithm. According to our proposed algorithm, the cluster is chosen on the bases of residual energy and the distance from the base station. On the basis of energy consumption and network lifetime we then compare the performance of our proposed algorithm with O-LEACH.